PENGARUH PENGALAMAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BPKDBADAN PENGELOAAN KEUANGAN DAERAH KABUPATENTAKALAR - Maya Silviani; Abd Rahman Rahim; Ismail Rasulong (Universitas Muhammadiyah Makassar, 2019)
MAYA SILVIANI, 2018, Effect of Experience and Work Environment on Employee Performance at Office BPKD (Local Financial Management Agency) Kab.Takalar, Thesis of Faculty of Economics and Business Faculty of Muhammadiyah University of Makassar. The type of data obtained through the questionnaire as a research instrument that describes the work experience, work environment and performance Employees. This study aims to find out how the experience and work environment affect the performance of employees at the office of BPKD (Local Financial Management Agency) Kab.Takalar. The results showed that the value of R Square is equal to 0.671 or 67.1%. This means variations in the power of influence of variables X1 (Experience) and X2 (Environment) of 67.1% of the variable Y (Performance). The remaining 32.9% is determined by other variables not examined in this study. This research model is stated to be good because the determinant coefficient value is close to 100% or 1. The results of the research show that the R Square value is 0.671 or 67.1%. This means variations in the power of influence of variables X1 (Experience) and X2 (Environment) of 67.1% of the variable Y (Performance). The remaining 32.9% is determined by other variables not examined in this study. This research model is stated to be good because the determinant coefficient value is close to 100% or 1